Recurrent Fusions Between YAP1 and KMT2A in Morphologically Distinct Neoplasms Within the Spectrum of Low-grade Fibromyxoid Sarcoma and Sclerosing Epithelioid Fibrosarcoma. (May 2020) - Puls, Florian; Agaimy, Abbas; Flucke, Uta; Mentzel, Thomas; Sumathi, Vaiyapuri P.; Ploegmakers, Marieke; Stoehr, Robert; Kindblom, Lars-Gunnar; Hansson, Magnus; Sydow, Saskia; Arbajian, Elsa; Mertens, Fredrik
Abstract : Sclerosing epithelioid fibrosarcoma (SEF) is an aggressive soft tissue sarcoma. In the majority of cases, there is overexpression of MUC4, and most cases show EWSR1-CREB3L1 gene fusions. A subset of SEF displays composite histologic features of SEF and low-grade fibromyxoid sarcoma (LGFMS). These "hybrid" tumors are more likely to harbor the FUS-CREB3L2 fusion, which is also seen in most LGFMS. We, here, characterize a series of 8 soft tissue neoplasms with morphologic features highly overlapping with LGFMS and SEF but lacking MUC4 expression and EWSR1/FUS-CREB3L gene fusions. Seven tumors showed fusions of the YAP1 and KMT2A genes, and 1 had a fusion of PRRX1 and KMT2D ; all but 1 case displayed reciprocal gene fusions. At gene expression profiling, YAP1 and KMT2A / PRRX1 and KMT2D tumors were distinct from LGFMS/SEF. The patients were 4 female individuals and 4 male individuals aged 11 to 91 years. Tumors with known locations were in the lower extremity (5), trunk (2), and upper extremity (1); 3 originated in acral locations. Tumor size ranged from 2.5 to 13 cm. Proportions of SEF-like and LGFMS-like areas varied considerably among tumors. All tumors that showed infiltrative growth and mitotic figures per 10 HPFs ranged from 0 to 18. Tumor necrosis was present in 1 case. Follow-up was available for 5 patients (11 to 321 mo), 2 of whom developed local recurrences, and 1 died of metastatic disease. The clinical behavior of these soft tissue sarcomas remains to be further delineated in larger series with extended follow-up; however, our limited clinical data indicate that they are potentially aggressive. Abstract : Supplemental Digital Content is available in the text.